Student perspectives on groupwork - Rees, Paul (Groupwork, 2012)
The educational system has a crucial role in developing groupwork skills in children and young people which will, in time, assist in the broader use of groupwork within society. Many educational establishments have for some years routinely employed groupwork pedagogy yet there has been limited research on how students actually perceive groupwork. This paper reports on student attitudes toward groupwork (n=248) within the context of a school improvement initiative. Staff from three schools met to reflect on their own practice of classroom groupwork. A questionnaire was subsequently developed and administered to elicit the general attitude of the students towards groupwork as well as their views on competition, interdependence, accountability, learning outcomes, group composition, teacher involvement, citizenship, and learning styles. Overwhelming support for groupwork was found within the cohort. Groupwork is viewed as enjoyable, preferable to individual work, a teaching strategy that can be engaged with, beneficial to learning, an aid to concentration during learning, helpful for memorising learning objectives and beneficial for life post-school. The paper discusses emerging themes and implications for the future.